2018
DOI: 10.20944/preprints201805.0351.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PPARgamma Expression is Diminished in Macrophages of Recurrent Miscarriage Placentas

Abstract: PPAR belongs to the group of nuclear receptors which is expressed in the trophoblast and together with other factors is responsible for the maintenance of pregnancy. Apart from that PPAR is also a main factor for macrophage polarization. The aim of this study was to investigate the combined expression pattern and frequency of PPAR under physiological circumstances and in spontaneous and recurrent miscarriages in the trophoblast and in maternal macrophages of the decidua. Human placental tissues of the first… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…As the second largest decidual leukocyte population in early pregnancy, macrophages play important roles in regulation of trophoblast biological functions 3 , 45 - 47 . Macrophages can be divided into M1 and M2 subtypes, and ours and other studies have confirmed the abnormal distribution of M1-Mφ in RSA 3 , 4 , 20 , 48 , 49 . A previous study indicated that activated macrophages affect trophoblast function and placental development, which may result in various adverse pregnancy outcomes 50 .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…As the second largest decidual leukocyte population in early pregnancy, macrophages play important roles in regulation of trophoblast biological functions 3 , 45 - 47 . Macrophages can be divided into M1 and M2 subtypes, and ours and other studies have confirmed the abnormal distribution of M1-Mφ in RSA 3 , 4 , 20 , 48 , 49 . A previous study indicated that activated macrophages affect trophoblast function and placental development, which may result in various adverse pregnancy outcomes 50 .…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, M2-Mφ can promote EMT of trophoblasts by secreting G-CSF, thereby enhancing their invasion and migration capabilities 18 . Numerous studies have shown that macrophages in RSA exhibit abnormal polarization status, which manifests as a high proportion of M1-Mφ or a decline in M2-Mφ in the decidua 3 , 4 , 19 , 20 . It was also reported that M1-Mφ can inhibit the invasion and migration of trophoblasts by secreting cytokines such as TNF-α 14 .…”
Section: Introductionmentioning
confidence: 99%
“…All the experiments were repeated at least three times. *P < 0.05, **P < 0.01 and ***P < 0.001 was characterized by impaired trophoblast migration and invasion abilities, and abnormal polarization of macrophages (increased M1 subtype and decreased M2 subtype) in placenta (Vishnyakova et al 2019;Przybyl et al 2016;Li et al 2016a;Buckley et al 2016;Kolben et al 2018). HTR-8/SVneo and JEG-3 cell lines have been widely used as in vitro models of trophoblasts in preeclampsia (Xu et al 2019;Zhang et al 2020c;Zhou et al 2020;Abbas et al 2020;Oh et al 2020;Zeng et al 2020;Zheng et al 2020a), and many studies investigating preeclampsia were based on the proliferation, migration, and invasion of trophoblasts (Xu et al 2019;Xue et al 2020;Zhou et al 2020;Abbas et al 2020;Oh et al 2020;Zeng et al 2020;Zhang et al 2019;Jiang et al 2020;Zheng et al 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of preeclampsia is also associated with dysfunction of the immune system, such as elevated inflammatory cytokines and altered monocyte-macrophage system (Vishnyakova et al 2019). More pro-inflammatory (M1) and less anti-inflammatory (M2) macrophages were observed in placenta in preeclampsia models, and this abnormal polarization state of macrophages could lead to dysfunction of trophoblasts, which may contribute to the impaired trophoblast invasion and spiral artery remodeling in preeclampsia (Przybyl et al 2016;Li et al 2016a;Buckley et al 2016;Kolben et al 2018). In addition, induction of M2 macrophage polarization was shown to assist successful pregnancy in a preeclampsia rat model (Li et al 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent miscarriage (RM) is an obstetric disease with a prevalence of 3% in women of childbearing age. The condition is associated with parental chromosomal anomalies, uterine abnormalities, endocrine factors, thrombophilia, cervical insufficiency and immunological disorders [1][2][3][4][5][6]. Of the various RM-related immunological disorders, antiphospholipid antibody syndrome (APS) is the most common [7,8].…”
Section: Introductionmentioning
confidence: 99%